State Supervision of Urban Construction: Modern Realities - M. Vasylchenko, Yurii (International Journal of Sustainable Construction Engineering and Technology, 2022)
The article is devoted to the study of the concept of state supervision and control in the field of urban planning. The methodological basis of the study is general and special methods of scientific knowledge. The system method, analysis and synthesis, grouping, and structural-logical method also became the basis of the The practical significance of the obtained results is that they are of both scientific-theoretical and practical interest and can be used in: research; lawmaking (conclusions and recommendations can be the basis for the adoption of bills).